anonymous
  • anonymous
Solve, using the substitution method. 4x + 2y = 11 x – 2 = – 2y A. (3, -1/2) B. (0, -2) C. (0, -11/2) D. (7, -5/2) I KNOW FOR SURE IT IS EITHER C OR B I WILL MEDAL AND FAN!
Mathematics
  • Stacey Warren - Expert brainly.com
Hey! We 've verified this expert answer for you, click below to unlock the details :)
SOLVED
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
schrodinger
  • schrodinger
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
anonymous
  • anonymous
@livias.random
anonymous
  • anonymous
i am sure it is c
anonymous
  • anonymous
@livias.random

Looking for something else?

Not the answer you are looking for? Search for more explanations.

More answers

anonymous
  • anonymous
i just need u to check so i can have some comfort lol :)
anonymous
  • anonymous
is i am wrong can u plz tell me how? thx
anonymous
  • anonymous
if i am wrong i mean***
anonymous
  • anonymous
x – 2 = – 2y x = -2y + 2 4(-2y + 2) + 2y = 11 -8y + 8 + 2y = 11 -6y + 8 = 11 -6y =3 y = -1/2 x = -2y + 2 x = -2(-1/2) + 2 x = 1 + 2 x = 3 (3,-1/2)
anonymous
  • anonymous
oh snap
anonymous
  • anonymous
So I got a, but I could have made a stupid mistake somewhere, do you want to show me your working?
anonymous
  • anonymous
yes one sec let me type it
anonymous
  • anonymous
x – 2 = – 2y x = -2y + 2 4(-2y + 2) + 2y = 11 -8y + 8 + 2y = 11 -6y + 8 = 11 -6y =3 y = -11/2 x = -2y + 3 x = -2(-1/2) + 2 x = 0+1 x = 0 OMG I KNOW WHAT I DID WRONG U WERE RIGHT!
anonymous
  • anonymous
x – 2 = – 2y 0, -11/2 0 - 2 = -2 (-11/2) -2 = 22/2 -2 = 11 No - x – 2 = – 2y 3, -1/2 3 - 2 = -2 (-1/2) 1 = 2/2 1 = 1 Yes
anonymous
  • anonymous
AWESOME
anonymous
  • anonymous
ON THE SECOND PART I SAID -11/2 instead of -1/2
anonymous
  • anonymous
YES
anonymous
  • anonymous
thx for cheking me!
anonymous
  • anonymous
No worries :)

Looking for something else?

Not the answer you are looking for? Search for more explanations.